Reading Capital: Foucault, Benjamin, Marx - Simoncini, Alessandro (2021)
Foucault and Benjamin exploited different themes and categories from Marx’s Capital, in accordance with their topics of interest and theoretical and political options. Foucault concentrated on the analysis of the relations of production as it concerned the disciplining of the working class by capital. Benjamin, based on the commodity fetishism, on the fascination of consumption and the mere patent consumer display in department stores. Both interpretations of Marx are treated in this article as complementary and convergent. In effect, starting from Marxian foundations, they allow us to trace a well-equipped genealogy of the submission of living beings to the modern relation of capital: a submission that continues under new forms in current capitalism. This text ends concluding this, opening a path yet to explore at the same time.